Analysis Of Profile And Growth Of Retail Government Bond Investors (Ori Bonds) From Ori001 To Ori015 Periods - Najwa Paramitha Wimbyarto; Zaenal Arifin (Green Publisher Indonesia, 2024)
Retail Government Bonds or ORI have become one of the investment instrument options officially launched by the Indonesian Government and protected by the law for Indonesian Citizens. With the existence of investment instruments issued by the government intended for the sustainability of the Indonesian economy, it is necessary to consider the involvement of Indonesian Citizens as investors in these Government Bonds. The purpose of this research is to determine the development and changes in the profile of ORI investors, both in terms of Demographic and Geographic classification, as the issuance of ORI progresses. The research method used is Descriptive Research through data analysis using Microsoft Excel and Google Spreadsheets as analytical tools. The results obtained through the analysis show that the profile of ORI investors in ORI001-ORI015 has experienced development during each issuance period, but no significant changes were found in the profile of ORI investors.